(untitled) (Journal of Computational Innovation and Analytics (JCIA), 2023)
Although e-commerce is being utilised, its application expanded exponentially during the pandemic due to government restrictions on mobility. Most of the existing literature points to the effect of perceived usefulness and ease of use toward attitudes that affect the intention to use technology. Issues surface relative to the effect of customers’ trust in the system and the risks involved. Using Structural Equation Modelling (SEM), the study aimed to investigate the effect of these factors on users’ intention to use online shopping. Specifically, it looks into the effect of trust and risk on attitude and intention. Results established that trust affects attitude but not intention, while risk did not significantly affect both. With the online experience over time, consumers generally view e-commerce as easy and useful, especially in acquiring significant information about the product and services and navigating through e-commerce tools. The respondents are aware that there is risk in online transactions such that they prefer to pay cash or GCash upon delivery. However, the effect of risk was not supported partly due to the mobility restrictions during the pandemic. This highlights the need to improve e-commerce designs for consumer protection and more pronounced government policies on online transactions.